The Dimensions API: a domain specific language for scientometrics research - Kövári, Adam; Pasin, Michele; Meduna, Alexander (Frontiers in Research Metrics and Analytics, 2025)
We describe the Dimensions Search Language (DSL), a domain-specific language for bibliographic and scientometrics analysis. The DSL is the main component of the Dimensions API (version 2.12.0), which provides end-users with a powerful, yet simple-to-learn and use, tool to search, filter, and analyze the Dimensions database using a single entry point and query language. The DSL is the result of an effort to model the way researchers and analysts describe research questions in this domain, as opposed to using established paradigms commonly used by software developers e.g., REST or SOAP. In this article, we describe the API architecture, the DSL main features, and the core data model. We describe how it is used by researchers and analysts in academic and business settings alike to carry out complex research analytics tasks, like calculating the H-index of a researcher or generating a publications' citation network.